Historical narrative, decoloniality, and polyphony in Management and Organization Studies: a theoretic-methodological approach - Ítalo da Silva; Elisabeth Cavalcante dos Santos (BBR: Brazilian Business Review)
This article aims to propose a polyphonic decolonial historical approach to Management and Organization Studies (MOS), relating the theoretical-methodological aspects of the historical perspective with the decolonial option. We suggest a conceptual dialogue between the historiographical approach and MOS. We aimed to reflect on the possibilities for improving the organization theory, emphasizing the methodological concern with polyphony in historical studies. As a result, epistemological limitations in the use of history are presented when associated with MOS that is necessary to be overcome. We assume a position of understanding the history composed of narratives as fragmented representations of the past. Also, we articulate the ethical-political option of decoloniality for the co-construction of historical narratives about translocal practical-knowledge in management - towards pluriversal transmodernity. The article contributes to epistemic and methodological (re)orientations engaged in the context of (1) local/regional research-teaching (2) through the theory and practice of management in (3) rescuing the sociocultural identity.